Telaah Potensi Fibrosis Paru pada Penyintas Infeksi COVID-19 Secara Bioinformatik dengan Pensejajaran Sekuen Gen Pengkode Protein Spike Sars-Cov-2 dan Sars-Cov - Arman Maulana Siddik; Dina Mulyanti; Suwendar (UNISBA Press, 2023)
Abstract. SARS-CoV-2 is a novel virus that causes Coronavirus Disease 2019 (COVID-19). Compared to the SARS-CoV, SARS-CoV-2 has similarities in the total length of the spike protein, which consists of 1273 amino acids. The aim of this research is to compare the similarities or differences in the gene sequences encoding the S protein of SARS-CoV-2 and SARS-CoV, particularly in the RBD region, and to analyze the potential of pulmonary fibrosis in COVID-19 survivors based on the bioinformatics sequence alignment of the Spike protein gene sequences of SARS-CoV-2 and SARS-CoV. The research methodology employed is a bioinformatics study, starting with the retrieval of the gene sequences encoding the S protein of SARS-CoV-2 and SARS-CoV from the National Center for Biotechnology Information (NCBI) database. The sequences of both viruses are aligned using the Clustal Omega to compare the gene sequence encoding the S protein of SARS-CoV-2 to the gene encoding S protein in SARS-CoV. The base sequences that was is the RBD region. The sequence alignment of the base sequences encoding the S protein reveals differences in the DNA sequence in the region surrounding the RBD, specifically at positions 319-541. These differences in the sequence alignment of the gene sequences encoding the S protein between SARS-CoV-2 and SARS-CoV pose a risk for the occurrence of pulmonary fibrosis in COVID-19 survivors due to significant genetic variations between the two viruses. Abstrak. SARS-CoV-2 merupakan jenis virus baru penyebab penyakit Coronavirus Disease 2019 (COVID-19). SARS-CoV-2 dibandingkan dengan SARS-CoV karena memiliki kemiripan dengan panjang total protein spike pada SARS-CoV-2 adalah 1273 asam amino. Tujuan penelitian ini adalah untuk membandingkan kesamaan atau perbedaan sekuen gen pengkode protein S SARS-CoV-2 dan SARS-CoV pada bagian RBD serta menganalisis potensi fibrosis paru pada penyintas infeksi COVID-19 berdasarkan pensejajaran sekuen gen protein Spike SARS-CoV-2 dan SARS-CoV secara bioinformatik. Metode yang digunakan dalam penelitian ini adalah studi bioinformatik, diawali dengan pencarian urutan gen pengkode protein S SARS-CoV-2 dan SARS-CoV dari laman National Center for Biotechnology Information (NCBI). Dilanjutkan dengan pensejajaran kedua virus tersebut menggunakan Clustal Omega untuk membandingkan urutan gen pengkode protein S SARS-CoV-2 dengan gen yang mengodekan protein S pada SARS-CoV. Urutan basa yang dianalisis adalah daerah RBD. Pensejajaran urutan basa pengkode protein S menunjukan adanya perbedaan urutan DNA pada daerah sekitar RBD yaitu pada posisi 319-541. Perbedaan hasil pensejajaran sekuen DNA protein S dari SARS-CoV-2 dan SARS-CoV tersebut memiliki indikasi efek yang berbeda pada penyintas infeksi COVID-19 karena adanya variasi genetik yang signifikan antara kedua virus tersebut.